Optimization of process parameters for the production of citric acid using sewage sludge as major fermentation media - Mohamad Hanapi, Nur Hanis; Alam, Md Zahangir; Abdul Karim, Mohamed Ismail (Academic Journals, 2011)
A research was conducted on liquid state bioconversion for the production of citric acid using sewage treatment plant (STP) sludge as the main substrate with supplementation of sucrose as co-substrate. Three parameters were examined to determine the best process optimization conducted in two liter (2L) bioreactor. Two level factorial designs with three parameters were applied for the fermentation. It was carried out using local isolates of Aspergillus niger strain O103A at room temperature (30 to 32°C),agitation was set at three different values which are 100, 200 and 300 rpm. Initial pH for fermentation was set at 5 and it was further adjusted to three levels which are 2, 3 and 4 on the second day of the fermentation. Another parameter was aeration where 1, 1.5 and 2 vvm were introduced. The fermentation was carried out for five days. The maximum yield of citric acid obtained throughout the fermentation was 23.68 g/L, which is due to low pH, low agitation and high aeration values.